Organizer, presenter and mediator of satellite stakeholder online event - Vasquez Christodoulou, Marlen (My University, 2026)
In collaboration with Dr Panayiotis Kasapidis and Dr Christina Pavloudi, Hellenic Centre for Marine Research Title of the event: “Molecular tools for bioassessment of aquatic ecosystems”